IMPACT OF SPIRITUAL REFORMS ON ENSURING GENDER EQUALITY - Akilova Ogilkhon Mirzapayasovna (Journal Park Publishing, 2023)
Our country is carrying out comprehensive reforms aimed at renewing the life of society, raising its spiritual sphere, modernizing it on the basis of modern science and national spiritual values. In this process, women are considered to be decisive force in ensuring the effectiveness of the spiritual factors of society. The article covers this issue in detail.
Keywords: spirituality, spiritual factors, civil society, globalization, spiritual immunity, “mass culture”, gender equality.